Management Strategy for Distributing Questionnaires and Interview Guidelines in the Research Data Collection Process - Sunarya, Po. Abas; Marantika, George Iwan; Faturahman, Adam (APTISI Transactions on Management (ATM), 2018)
Writing can mean lowering or describing graphic symbols that describe a language understood by someone. For a researcher, management of research preparation is a very important step because this step greatly determines the success or failure of all research activities. Before a person starts with research activities, he must make a written plan commonly referred to as the management of research data collection. In the process of collecting research data, of course we can do the management of questionnaires as well as the preparation of interview guidelines to disseminate and obtain accurate information. With the arrangement of planning and conducting interviews: the ethics of conducting interviews, the advantages and disadvantages of interviews, the formulation of interview questions, the schedule of interviews, group and focus group interviews, interviews using recording devices, and interview bias. making a questionnaire must be designed with very good management by giving to the information needed, in accordance with the problem and all that does not cause problems at the stage of analysis and interpretation.